Studies on Routine Urine Analysis of Urinary Tract Infection - and V.L. Deshmukh, A. M. Pande, R. T. Chavan, Muley S. S. (Recent Research in Science and Technology, 2011)
The data obtained form routine urine analysis Viz physical examination, chemical examination and microscopic examination revealed that, in case of physical examination of urine sample is yellow to milky colour was observed while in case of appearance it was turbid to hazy where as putrefied odor was observed in all sample n=10. The data obtained form chemical examination indicates presence of albumin in all sample. Bile salt is present only one sample. The data obtained form microscopic examination revealed that pus cell count increases in all samples suffering from Urinary tract infection (uti).